Advanced Refinement Techniques for Optimal Sugar Crystal Production: Teknik Pemurnian Tingkat Lanjut untuk Produksi Kristal Gula yang Optimal - Arman, Shiva Haiqa; Hudi , Lukman; Akhairunnisa, Rahmaniah (Procedia of Engineering and Life Science, 2024)
This study investigates the transformation of sap into crystal sugar, emphasizing the enhancement of sugar quality through meticulous purification processes. The methodology involved a sequential observation of various production stages: milling, refining, evaporation, cooking, and finishing, each integrated with a quality assurance analysis to maintain high product standards. Critical parameters such as Brix, pol, temperature, pH, color balance, phosphate, sulfur content, and turbidity were rigorously monitored. Findings indicate that strategic control of these parameters at the purification stage significantly reduces impurities, thus ensuring the consistency and quality of the final crystal sugar product. The implications of this study suggest that systematic quality controls and precise parameter management may lead to improvements in sugar refinement processes, with potential applications in similar manufacturing environments globally. Highlights: Quality assurance: Regular analysis of sap quality ensures consistent production standards. Purification stage: Vital parameters such as Brix, pH, and color balance are monitored for impurity removal. Product quality: Maintenance and adjustments based on analysis ensure high-quality crystal sugar output. Keywords: Crystal Sugar, Cane, Crystallization